2014
DOI: 10.1080/08959420.2014.854583
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Partnership in Age-Friendly Cities: Two Case Studies From Quebec, Canada

Abstract: This article aims to explain the collaborative partnership conditions and factors that foster implementation effectiveness within the age-friendly cities (AFC) in Quebec (AFC-QC), Canada. Based on a community-building approach that emphasizes collaborative partnership, the AFC-QC implementation process is divided into three steps: (1) social diagnostic of older adults' needs; (2) an action plan based on a logic model; and (3) implementation through collaborations. AFC-QC promotes direct involvement of older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 5 publications
0
60
0
7
Order By: Relevance
“…Demographic changes worldwide, including population aging and urbanization, draw attention to processes of well-being in older age, linked to active aging, community engagement, and life satisfaction. The sense of community can have implications for identifying best practices and sustainable interventions (Garon et al, 2014;Chan and Cao, 2015). Social connectedness and inclusion have been identified as major benefits of agefriendly initiatives (Menec et al, 2011;Emlet and Moceri, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Demographic changes worldwide, including population aging and urbanization, draw attention to processes of well-being in older age, linked to active aging, community engagement, and life satisfaction. The sense of community can have implications for identifying best practices and sustainable interventions (Garon et al, 2014;Chan and Cao, 2015). Social connectedness and inclusion have been identified as major benefits of agefriendly initiatives (Menec et al, 2011;Emlet and Moceri, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research focused mainly on comparing age-friendly approaches [48] or assessment [49], detecting factors that assist communities in or hinder them from becoming age-friendly [50], explaining the collaborative partnership conditions and factors that foster implementation effectiveness [51], as well as identifying priorities for actions [52]. This research provided valuable information on most common projects that, for example in Manitoba, were related to outdoor spaces, buildings, communications and activities (e.g., walking groups, contacting isolated older adults) [52].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, other regions are developing age-friendly initiatives, including the State of South Australia, the Andalusian Province in Spain and the State of Sao Paulo in Brazil. Researchers from across disciplines, have identified that a participatory, collaborative style of governance is a key feature of the age-friendly model, with engagement needed at all levels of government (Lui et al 2009, Plouffe & Kalache 2011, Ball & Lawler 2014, Garon et al 2014. Other initiatives, with similarities to age-friendly city initiatives, have been reported on in the literature, such as the 'liveable communities' in the United States of America (USA) and 'lifetime neighbourhood' in the United Kingdom (Lui et al 2009).…”
Section: Introductionmentioning
confidence: 94%